2003
DOI: 10.1016/s0735-1097(02)02872-3
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis of mechanical prosthetic valve thrombosis

Abstract: These results indicate that FT is effective in most cases of PHVT, regardless of prosthesis or site involved. However, embolism, hemorrhage, and death were not uncommon after lytic therapy of left-sided PHVT, limiting its application to patients at high risk with alternative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 22 publications
1
72
0
8
Order By: Relevance
“…In adults, success is ≈75% with a 25% rate of complications such as bleeding, systemic thromboembolism, failure resulting in reoperation, and death. 335,336,[341][342][343][344][345][346] There is experience with thrombolytic therapy in children for thrombotic occlusion of prosthetic valves, and the results seem similar to the adult experience. 51a,345,347-351 The management of pediatric patients with valve thrombosis should mirror that outlined for adults in the ACC/AHA guidelines for management of patients with valvular heart disease and the eighth edition of the American College of Chest Physicians evidence-based clinical practice guidelines.…”
Section: Recommendations For Long-term Prevention Ofmentioning
confidence: 77%
“…In adults, success is ≈75% with a 25% rate of complications such as bleeding, systemic thromboembolism, failure resulting in reoperation, and death. 335,336,[341][342][343][344][345][346] There is experience with thrombolytic therapy in children for thrombotic occlusion of prosthetic valves, and the results seem similar to the adult experience. 51a,345,347-351 The management of pediatric patients with valve thrombosis should mirror that outlined for adults in the ACC/AHA guidelines for management of patients with valvular heart disease and the eighth edition of the American College of Chest Physicians evidence-based clinical practice guidelines.…”
Section: Recommendations For Long-term Prevention Ofmentioning
confidence: 77%
“…Despite the lack of randomized controlled prospective trials comparing surgery and thrombolytic therapy in the case of PVT, fibrinolysis has been recommended to critically sick patients with functional class III or IV, and high surgical operative risk as the class IIb recommendation (level of evidence: B) by ACC/AHA (1). The experience using thrombolysis has been summarized in recent European recommendations (2), review papers (3) and single center reports (4).…”
Section: Discussionmentioning
confidence: 99%
“…The argument in favor of surgery in NYHA functional class I or II patients is based on the low mortality in this group, as opposed to the high risk of embolism (12-17%) resulting from thrombolysis 7 . In a review of 200 articles on thrombolysis in PVT of left chambers, Lengyel et al found an initial success rate of 82%, with a thromboembolism rate of 12% and mortality rate of 10% 8 .…”
Section: Discussionmentioning
confidence: 99%